2000
DOI: 10.1007/pl00011685
|View full text |Cite
|
Sign up to set email alerts
|

Influence of perioperative blood transfusion on the prognosis of patients with gastric cancer receiving anticancer chemotherapy

Abstract: BACKGROUND: The deleterious effect of blood transfusions on survival has been reported in patients with cancers of various organs. However, it remains unclear whether there is any adverse effect of blood transfusion when the patients are administered anticancer drugs after surgery for gastric cancers.METHODS: Data from patients with gastric resection for advanced gastric cancer were retrospectively analyzed to determine the influence of perioperative blood transfusion on the survival rate. All patients were ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…This study has demonstrated that the acellular plasma fraction from stored packed erythrocytes promotes cellular proliferation, and Pan02 migration (surrogates for cancer growth and metastasis) promotes in vivo pancreatic cancer growth. Although previous clinical studies have shown similar conclusions,10, 17, 18, 45 these studies are difficult to interpret given the large number of variables inherent in any cancer patient population, including tumor biology, tumor stage, and untoward events during surgery, as well as innumerable host factors. Use of this well‐established immunocompetent model of pancreatic cancer29 has allowed us to control for many factors that cause clinical trials to be dismissed.…”
Section: Discussionmentioning
confidence: 78%
“…This study has demonstrated that the acellular plasma fraction from stored packed erythrocytes promotes cellular proliferation, and Pan02 migration (surrogates for cancer growth and metastasis) promotes in vivo pancreatic cancer growth. Although previous clinical studies have shown similar conclusions,10, 17, 18, 45 these studies are difficult to interpret given the large number of variables inherent in any cancer patient population, including tumor biology, tumor stage, and untoward events during surgery, as well as innumerable host factors. Use of this well‐established immunocompetent model of pancreatic cancer29 has allowed us to control for many factors that cause clinical trials to be dismissed.…”
Section: Discussionmentioning
confidence: 78%
“…In patients with gastric cancer, the postoperative 5-year survival rates are reportedly 49-65% for transfused patients and 62-77% for non-transfused patients (p < 0.05) [10,11] . However, some studies have reported that there was no association between perioperative blood transfusion and prognosis [12][13][14][15] . In this study, the OS and DFS of patients who received perioperative blood transfusions was significantly shorter than that of patients who did not.…”
Section: Discussionmentioning
confidence: 99%
“…Previous data on blood transfusion and clinical outcome in upper gastrointestinal cancers are inconclusive. Some studies have shown an association between perioperative blood transfusion and poor prognosis [10], whereas others have reported no such relationship [11][12][13][14][15] . Postulated explanations for a relationship between perioperative blood transfusion and poor prognosis have included transfusion-related immunomodulation: immunosuppressive or proinflammatory changes [16] .…”
Section: Introductionmentioning
confidence: 99%
“…A reduced overall survival after TFs for patients undergoing resections of pancreatic [12], gastric [11], or colorectal cancer [35] was not detected in other studies of patients with similar diagnoses [31,36,37]. In an observational analysis of a prospective trial of patients undergoing colorectal cancer resections, TF led to a reduction in overall survival, but not in cancer recurrence rate [14].…”
Section: Discussionmentioning
confidence: 94%
“…Contemporary hepatectomy-related PRBC transfusion rates have been described as 35% [29], 34% [3], 17% (since 1995) [6], or 11% [30], compared with 16% in this experience. TF rates after gastrectomy are 35% [11] or 33% [31] in recent reports, compared with 30% in this series; TF rates after esophagectomy (33% in this report) may be higher, such as 46% [10]. The category of "other" resections in our analysis includes lower-risk procedures such as large bowel resections (TF rate: 14%) as well as complex procedures for which specific surgical oncology input was requested in consultation, which precludes a conclusive analysis of this heterogeneous subgroup.…”
Section: Discussionmentioning
confidence: 99%